Bacterial spoilage profiles in the gills of Pacific oysters (Crassostrea gigas) and Eastern oysters (C. virginica) during refrigerated storage. (September 2019) - Chen, Huibin; Wang, Meiying; Yang, Chengfeng; Wan, Xuzhi; Ding, Huihuang H.; Shi, Yizhuo; Zhao, Chao
Abstract: Microorganisms harbored in oyster gills are potentially related to the spoilage and safety of oyster during storage. In this study, the microbial activities and pH changes of the gills of the two species, Crassostrea gigas and C. virginica, harvested from three different sites were determined and sensory evaluation was conducted during refrigerated storage. The bacteria in gills with an initial aerobic plate count (APC) of 3.1–4.5 log CFU/g rose remarkably to 7.8–8.8 log CFU/g after 8-days of storage. The APC of Enterobacteriaceae increased from 2.5 to 3.6 log CFU/g to 4.5–4.8 log CFU/g, and that of lactic acid bacteria (LAB) fluctuated in the range of 1.4–3.0 log CFU/g during the whole storage period. The results of sensory analysis indicated that the oysters had 8-days of shelf-life and that the gill presented the fastest deterioration rate. The pH of all samples showed a decrease in the early stages followed by an increased after 4-days of storage. The dynamic changes in microbial profiles were depicted to characterize gill spoilage by Illumina Miseq sequencing to characterize gill spoilage. The results revealed that oysters harvested at different sites showed common bacterial profiles containing Arcobacter, Spirochaeta, Pseudoalteromonas, Marinomonas, Fusobacterium, Psychrobacter, Psychromonas, and Oceanisphaera when spoiled, especially, among which Psychrobacter and Psychromonas (psychrotrophic genus) were represented as the most important gill spoiled bacteria during refrigerated storage, and Arcobacter with pathogenic potential was the dominated bacteria in all spoiled oysters. The consumption quality and safety of refrigerated oysters could be greatly improved by targeted control of bacteria in oyster gills according to the results the present study provided. Graphical abstract: Image 1 Highlights: Bacterial spoilage profiles of Pacific and Eastern oysters gills were determined. Illumina Miseq sequencing was used to reveal the spoilage bacterial profiles. Psychrobacter and Psychromonas were the most important gill spoiled bacteria. Arcobacter with pathogenic potential was the dominated bacteria in spoiled oysters.